Filozofia moralności Immanuela Kanta w świetle teorii językoznawstwa kognitywnego - Gierszewska, Magdalena (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2011)
The purpose of this article is to present unusually novel approach to Kantian ethics. Linguists George Lakoff and philosopher Mark Johnson are describing the most important concepts of the Kantian work of morality, thanks to their development of cognitive theory of metaphors. It helps the readers to discover its assumptions and aims in much more understandable way. The article shows the phenomenon of the theory of metaphors in the Kantian ethics.
Keywords: Cognitive science; Kant